Update on: proteome analysis in thyroid pathology – part II: overview of technical and clinical enhancement of proteomic investigation of the thyroid lesions. (2nd November 2018) - Piga, Isabella; Casano, Stefano; Smith, Andrew; Tettamanti, Silvia; Leni, Davide; Capitoli, Giulia; Pincelli, Angela Ida; Scardilli, Marcella; Galimberti, Stefania; Magni, Fulvio; Pagni, Fabio
ABSTRACT: Introduction : An accurate diagnostic classification of thyroid lesions remains an important clinical aspect that needs to be addressed in order to avoid 'diagnostic' thyroidectomies. Among the several 'omics' techniques, proteomics is playing a pivotal role in the search for diagnostic markers. In recent years, different approaches have been used, taking advantage of the technical improvements related to mass spectrometry that have occurred. Areas covered : The review provides an update of the recent findings in diagnostic classification, in genetic definition and in the investigation of thyroid lesions based on different proteomics approaches and on different type of specimens: cytological, surgical and biofluid samples. A brief section will discuss how these findings can be integrated with those obtained by metabolomics investigations. Expert commentary : Among the several proteomics approaches able to deepen our knowledge of the molecular alterations of the different thyroid lesions, MALDI-MSI is strongly emerging above all. In fact, MS-imaging has also been demonstrated to be capable of distinguishing thyroid lesions, based on their different molecular signatures, using cytological specimens. The possibility to use the material obtained by the fine needle aspiration makes MALDI-MSI a highly promising technology that could be implemented into the clinical and pathological units.